Bitcoin: uma análise da trajetória do dinheiro - Do escambo às criptomoedas : um estudo das legislações vanguardistas e suas influências sobre o projeto de lei n. 2.303/15. - Mangueira, Anna Cecília dos Santos (2018)
Bitcoin, derived from anthropocentric movements that believed in privacy through cryptography above regulation, for some, emerged as a future substitute for money and this has caused nation states a certain instability, given the invasion of a form of payment / a virtual currency that does not depend on state bonds and, therefore, removes part of the centralized supervision fostered by the activity of the Central Bank and banking institutions in general. Faced with the problems arising from the matter, the State of New York has created, in an avant-garde way, BitLicense, which is a series of regulations so that the Exchanges (companies that act with the exchange of virtual currencies) could function in its territory. In turn, the Court of Justice of the European Union was prompted to decide on the feasibility or non-application of Value Added Tax on the activity of a Swiss Exchange. In the face of these manifestations, this research seeks to demonstrate if the Brazilian legislature has taken into account such decisions, as well as whether there is movement by the national legislature, or any state organs, in order to guarantee a minimum intervention. Regarding the last analysis, it is sought to verify that Bill No.2303, of 2015, of Mr. Aureo, which deals with the inclusion of virtual currencies and air mileage programs in the definition of payment arrangements under the supervision of the Central Bank has made some changes and if this fits into some of the decisions taken internationally. For the accomplishment of the present research will be used the methodology of qualitative research of bibliographical revision and analysis of decisions, will also be used mechanism of research Patch Dependence, with the objective to verify the historical reasons that the decisions that will be analyzed. The theoretical framework used is derived from texts by Milton Friedman.